Analisis Performansi Reaktor Gasifikasi Updraft Dengan Bahan Bakar Tempurung Kelapa - Hendra Gunawan, I Gede; Sucipta, Made; Suprapta Winaya, I Nyoman (Jurnal Mettek: Jurnal Ilmiah Nasional dalam Bidang Ilmu Teknik Mesin; Vol 1 No 2 (2015), 2015)
Coconut shell can be easily obtained because of abundant and for now it is only used as charcoal only. By knowing the chemical composition and content contained in coconut shell, the material can be used as a source of alternative energy through a gasification process gasifikasi.Ada several types ie Fixed Bed Gasification updrafts, Downdraft and Crossdraft. In this study the gasification process using a reactor made of black steel with high dimensional reactor 70 cm from the bottom of the buffer to cover the top of the reactor and the reactor diameter of 8 inches. Air flow rate is used as the gasification agent, according to the theory stoichiometry of 37 lpm (liters per minute). Fuel used for the gasification process is coconut shell. From the research menunujukan gasification process can produce gas capable of combustion (CO, CH4, H2) continuously for 900 seconds, the resulting actual FCR is 9.716 kg / h, which generates CO content = 13.32%, 1.52% CH4 = , H2 = 4.68%, N2 = 37.09% and CO2 = 38.21%, 5.91 MJ of energy produced and the efficiency of gas by 28.8%. Updraft gasification process is still not perfect because of the results of the average temperature in the oxidation zone is 246,90C and CO2 = 38.21%, the gasification process refers more to the combustion process. Keywords : Performance reactor, gasification updrafts, coconut shell